Drug-Drug Interaction of Ergotamine with a Combination of Darunavir, Abacavir, and Lamivudine Causing a Fatal Vasospastic Ischemia. (19th December 2018) - Petit, Elisabeth; Schoonheydt, Karen; Meert, Philippe; Van Laer, Marie
Abstract : Ergotamine toxicity has become a rare condition which can be caused by, among others, drug-drug interaction. In this work we report a case with vasospastic ischemia induced by the wrongful combination of ergotamine with recently started Antiretroviral Therapy. Clinicians were not aware that patient was self-medicating for years with medication containing ergotamine and caffeine for migraines. This diagnosis was established after evaluating the evolving 'and spreading' ischemia and CT scans and thoroughly interviewing patient's family. Treatment was started with intravenous nimodipine and intra-arterial sodium nitroprusside on the affected limbs. The patient developed severe limb ischemia, cerebral ischemia, and metabolic encephalopathy. Unfortunately no improvements were noticeable and due to evolving cerebral edema as a result of the ischemia, the patient developed brain herniation and died shortly after.